Retinal Nerve Fiber Layer Thinning Is Associated With Brain Atrophy: A Longitudinal Study in Nondemented Older Adults - Shi, Zhongyong; Zheng, Hailin; Hu, Jingxiao; Jiang, Lijuan; Cao, Xinyi; Chen, Yupeng; Mei, Xinchun; Li, Chunbo; Shen, Yuan (Frontiers in Aging Neuroscience, 2019)
Backgrounds: Abnormal retinal nerve fiber layer (RNFL) thickness has been observed in patients with Alzheimer’s disease (AD) and therefore suggested to be a potential biomarker of AD. However, whether the changes of RNFL thickness are associated with the atrophy of brain structure volumes remains unknown. We therefore set out a prospective investigation to determine the association between longitudinal changes of RNFL thickness and brain atrophy in nondemented older participants over a period of 12 months. Materials and Methods: We measured the RNFL thickness using optical coherence tomography (OCT) and brain structure volumes by 3T magnetic resonance imaging before and after 12 months. Cognitive function was assessed using the Chinese version of Mini-Mental State Examination and Repeatable Battery for the Assessment of Neurological Status. Associations among the changes of RNFL, brain structures and cognitive function were analyzed with Spearman correlation and multiple linear regression models adjusting for the cofounding factors. Results: Fifty old participants were screened and 40 participants (mean age 71.8 ± 3.9 years, 60% being male) were enrolled at baseline. Among them, 28 participants completed the follow-up assessments. The average reduction of RNFL thickness was inversely associated with the decrease of central cingulate cortex volume after the adjustment of age and total intracranial volume (ß = -0.41, P = 0.039). Specifically, the reduction of RNFL thickness in the inferior, not other quadrants, was independently associated with the decline of central cingulate cortex volume after the adjustment (ß = -0.52, P = 0.006). Moreover, RNFL thinning, central cingulate cortex atrophy and the aggregation of white matter hyperintensities were found associated with episodic memory in these older adults with normal cognition. Conclusions: RNFL thinning was associated with cingulate cortex atrophy and episodic memory decline in old participants. The longitudinal changes of RNFL thickness is suggested to be a useful complimentary index of neurocognitive aging or neurodegenerating.